Aplicación de la teoría de Dorothea Orem en el cuidado al paciente con cáncer gástrico - Naula Criollo, Carolina Lisbeth (2022)
ABSTRACT Gastric cancer is one of the most common types of cancer in Ecuador. According to statistical data from the INEC in 2018, it reported 1,687 cases of mortality, equivalent to 2.3%, responding to 9.8 cases per 100,000 inhabitants. Generally, patients present with an initial silent disease showing symptoms in advanced stages, which entails an unfavorable prognosis, altering the environments: physical, psychological, social, and spiritual, which is reflected in the decrease in their self-care and in the quality of life. The general objective is to describe Dorothea Orem's theory in the care of patients with gastric cancer through a bibliographic review according to the criteria of several authors. Eighty bibliographic sources from different databases were reviewed, and after applying inclusion and exclusion criteria, a sample of 60 bibliographic references was obtained, of which 34 were used for the triangulation process. Based on the results, nursing urgency is determined through Orem's three subsystems: totally compensatory, partially compensatory, and supportive- education necessary to relieve the most severe symptoms and support at a psychosocial level. In this way, care is included in a holistic to improving quality of life. NANDA diagnostic labels will be required, which will allow standardized care to be provided. Keywords: Gastric cancer, self-care, Nursing Care, Dorothea Orem Firmado electrónicamente por: MARCELA PATRICIA GONZALEZ ROBALINO